Oral and maxillofacial evaluation and management in cases of mandibular condyle fractures (Research, Society and Development, 2023)
Condylar fractures have a significant incidence among facial fractures. The condyle is part of the temporomandibular joint (TMJ) structure, which is responsible for mandibular movements, mastication and phonation. Therefore, in cases of fractures, it is necessary for the professional to make an adequate assessment through clinical findings and imaging tests, such as computed tomography, which allows to verify the location and extent of the fracture. With this, it will be possible to make a correct diagnosis and treatment plan. In this sense, the present study aims to address the methods of evaluation and the principles of treatment of mandibular condyle fractures, in order to have a favorable prognosis. To develop this article, research was carried out in the Google Scholar and SciELO databases in order to review the literature, with works from 2012 to 2022 in Portuguese and English. This review allowed us to verify that a detailed evaluation of the fracture is fundamental for the choice of therapeutic conduct. In addition, it was concluded that both conservative and surgical treatment are effective when correctly indicated by the surgeon.